E-Government Public Cloud Model (EGPCM) - Al-Hakkak, Nada M.; Shukur, Ban Salman; Shaker, Atheel Sabih (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
The concept of implementing e-government systems is growing widely all around the world and becoming an interest to all governments. However, governments are still seeking for effective ways to implement e-government systems properly and successfully. As services of e-government increased and citizensâ€™ demands expand, the e-government systems become more costly to satisfy the growing needs. The cloud computing is a technique that has been discussed lately as a solution to overcome some problems that an e-government implementation or expansion is going through. This paper is a proposal of a  new model for e-government on basis of cloud computing. E-Government Public Cloud Model EGPCM, for e-government is related to public cloud computing.